Konsep Desain Tempat Penampungan Sampah pada Jalan Tua Pati Naya Raya, Kota Palembang - Bintang, Trya; ., Firdaus; Mulyati, Ely (CV. Information Technology Training Center - Indonesia (ITTC), 2026)
Urban waste management is a serious challenge for large cities, including Palembang. Jalan Tua Pati Naya Raya is an area with high residential and commercial activity, resulting in increasing amounts of waste, but it is not yet supported by adequate temporary storage sites (TPS). This study aims to design an optimal TPS concept that complies with technical standards and is environmentally friendly to support sustainable waste management. The research methods include field observations, primary and secondary data collection, waste generation analysis, and design planning based on SNI 3242:2008 and Permen PUPR No. 03/PRT/M/2013. The analysis results show that waste generation increased from 31.97 m³/day in 2021 to 56.91 m³/day in 2025 and is projected to reach 117.49 m³/day in 2030. Based on these results, a Type II TPS with a minimum capacity of 100 m³/day is planned on an area of 200 m², equipped with sorting facilities, composting, a closed drainage system, and greening. This design is expected to improve the effectiveness of waste management and the environmental quality of the research area.